2023
DOI: 10.1002/aenm.202203982
|View full text |Cite
|
Sign up to set email alerts
|

Evaporated Self‐Assembled Monolayer Hole Transport Layers: Lossless Interfaces in p‐i‐n Perovskite Solar Cells

Abstract: Engineering of the interface between perovskite absorber thin films and charge transport layers has fueled the development of perovskite solar cells (PSCs) over the past decade. For p‐i‐n PSCs, the development and adoption of hole transport layers utilizing self‐assembled monolayers (SAM‐HTLs) based on carbazole functional groups with phosphonic acid anchoring groups has enabled almost lossless contacts, minimizing interfacial recombination to advance power conversion efficiency in single‐junction and tandem s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
52
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 105 publications
6
52
0
Order By: Relevance
“…As Figure a presents, these SAMs are characterized by a phosphonic acid head and carbazole group, which shows an outstanding hole transporting property. It has been reported that the phosphonic acid head in the SAMs is inclined to bind to the substrate, with the hydrophobic carbazole group facing upward to contact with the perovskite layer (Figure b) . Such arrangement of SAMs leads to a hydrophobic surface, which is confirmed by the contact angle measurement.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…As Figure a presents, these SAMs are characterized by a phosphonic acid head and carbazole group, which shows an outstanding hole transporting property. It has been reported that the phosphonic acid head in the SAMs is inclined to bind to the substrate, with the hydrophobic carbazole group facing upward to contact with the perovskite layer (Figure b) . Such arrangement of SAMs leads to a hydrophobic surface, which is confirmed by the contact angle measurement.…”
Section: Resultsmentioning
confidence: 59%
“…To obtain high-quality and bright perovskite films for constructing LEDs, suitable HTL materials need to be used. Self-assembled monolayer (SAM) materials have emerged as promising HTL materials for constructing high-performance perovskite optoelectronic devices in recent years. Here, we select two representative SAM materials as HTLs for depositing perovskite films in ambient air, i.e., 2PACz and MeO-2PACz.…”
Section: Resultsmentioning
confidence: 99%
“…Possible inhomogeneities such as unabsorbed SAM molecules can be removed by post-treatment, such as solvent washing. Recently, an interesting work reported that SAMs can be fabricated by vapor-phase deposition [60], which is also promising for future large-scale manufacturing.…”
Section: Uniform Coating Over Large-area Substratesmentioning
confidence: 99%
“…Focusing on hole transport materials, high efficiencies have been obtained with extremely thin organic HTMs such as poly­(4-butyltriphenylamine) (poly-TPD), poly­[ bis (4-phenyl)­(2,4,6-trimethylphenyl)­amine] (PTAA), and carbazole-based self-assembling monolayers (SAMs). For small areas (<1 cm 2 ), these devices often outperform those with inorganic HTM in terms of efficiency . However, the deposition of <5 nm thick organic layers over a large scale by solution processes, such as spin coating, dip coating, and slot-die coating, is challenging and prone to pinhole formation, especially in the case of textured surfaces such as those used by the Si PV industry.…”
Section: Introductionmentioning
confidence: 99%